(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article presents the results of the analysis of data on atmospheric air pollution in the city of Navoi based on the reporting data of the Monitoring Service for Atmospheric, Surface Water and Soil Pollution of the Center for Hydrometeorological Service of the Republic of Uzbekistan. Analyzed data on the study of the concentration of the main pollutants: dust, sulfur dioxide, carbon monoxide, nitrogen dioxide and oxide, as well as specific impurities and heavy metals.